Design 3-Dimentional LQR controller for a Hexacopter using LabVIEW - أبو قاسم كندة; صالح تيماء (Latakia University Journal -Engineering Sciences Series, 2020)
This paper focuses on the design of three controllers Hexacopter rotation angles around the three axes (x, y, z) in a three-dimensional space. This type of helicopter specifically "multi-rotors" has several characteristics such as vertical takeoff and landing, Mechanical simplicity, high ability to hover, and lightness of motion abilities, and it has big challenges with controlling it represented by its mathematical model which characterized as highly nonlinear, Under-actuated, and coupled. In this research, the control unit adopts a linear quadratic regulator (LQR) that achieves good stability and provides great energy savings depending on the function called the objective function. The target is minimizing this function by tuning it and calculating the gain value so that it optimizes the energy saving and response. The model was tested based on the LabVIEW simulation program, as well as the control and simulation design modules.